Flexible Micromanipulators and Micromanipulation - Cammarata, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint, "Flexible Micromanipulators and Micromanipulation," is a collection of 12 full research articles that provide insights into the latest development and applications in the field of micromanipulation which has important applications in areas, such as metal additive manufacturing, medical devices, and robotics. The topics of the reprint cover the design and fabrication of magnetic actuators, electromagnetic levitation systems, compliant manipulators and robots, micromanipulation of microparticles and microcapsules to characterize mechanical properties of microscale objects, and inchworm robot for inspection, assembly, and maintenance.